Simulation Versus Traditional Method Of Teaching On The Retention Of Birthing Care - Jyoti; AK Mamata Devi; Khushbu; Shalu (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Nursing is profession where practical and theoretical knowledge needs to be highly integrated and clinical practice is significant for the professional development of Nursing students. The shift from traditional instructional methods towards student-centered teaching challenges Nursing faculty to create learning experiences that will develop safe and competent graduates. Going out into the clinical field can be stressful for Nursing students. They know that mistakes can seriously affect a patient’s outcome. Nursing faculties are always looking for more effective teaching methods that enhance student knowledge and skills. Materials and Methods: Comparative research design was used to evaluatethe effectiveness of simulation based training versus traditional method of teaching on the retention of birthing care knowledge and skills. Convenience sampling technique was used to select 77 B.Sc Nursing Fourth Year students from SGT University Gurugram and R.R College of Nursing Gurugram.Results: The knowledge score for simulation group (23.05) was higher than traditional teaching group (17.87) at t = 31.08.The skill score for traditional teaching group (29.23) and simulation based training group (37.23) at t = 33.23.Simulation based training was more effective rather than traditional method of teaching in improving the retention birthing care knowledge and skills among students.Conclusion: Simulation based training has opened up a firsthand learning in a nursing profession. Evidencebased practices can be put into action by means of protocols and algorithms, which can then be practiced via simulation scenarios. The key to success in simulation training is integrating it into traditional education programmes.